Visitors’ behavioral patterns and the interactive models at the Penang house of music, Malaysia / Muhammad Ammar Maliki and Wahiza Abdul Wahid - Maliki, Muhammad Ammar; Abdul Wahid, Wahiza (Faculty of Art and Design, 2021)
As a world-class tourist destination, Penang or "The Pearl of Orient" is a very widely known state in Malaysia and abroad, where there are various notable attractions available in this state such as dazzling beaches, heritage landmarks, delightful street food, and several other. Nonetheless, there are several Malaysians who do not realize that there is a considerable number of interactive museums in the state of Penang. The interactive museums in Penang also provide top-notch and first-class collections and facilities that could lure local visitors and tourists from all over the world. Besides the city-state of Kuala Lumpur and Malacca which is becoming the center of attraction for tourists, Penang is another state that receives lots of tourists from numerous parts of the world. Through observation, tourists visit Malaysia, not only for their interest in Malaysian culture, heritage as well as foods but tourists from different parts of the world nowadays are heading towards museums for, they realize that museums offer many things they could learn from. In discussing museums, Penang offers museums of many kinds. The Penang House of Music, as an example, is Penang's most well-known interactive museum which features an unparalleled variety of interactive models. This interactive museum is one of the well-received museums in Penang by both local visitors and tourists. The interactive models introduced at the Penang House of Music are among the finest in Penang, which is discussed in this article. As one of the World Heritage Sites, the city of Georgetown, the capital of Penang, is believed to consist of the greatest number of interactive museums in Malaysia, which have the potential to expand aggressively. Other than discussing models of interactive museums, this article also analyzes the behavioral pattern of the visitors at the Penang House of Music, as these topics are linked to each other. This is because the models at the interactive museums influence the behavioral pattern of visitors in terms of attendance at the museums regardless of age, educational background plus the purpose of visit. The central issue in this paper will however emphasize more on the interactive models to relate to the museum’s effort in attracting more returners.